Comparison of CABAC rate estimation models for HEVC rate distortion optimisation. Issue 6 (1st March 2014) - Choi, Soonwoo; Chae, Soo‐Ik
Abstract : Eight models are compared for CABAC rate estimation for HEVC rate‐distortion optimisation, which are derived by changing three model variables such as the interval range distribution, the MPS range model and the model of generated bits per bin. It is found that the fractional bit model provides substantially better accuracy of rate estimation than the integer model for generated bits per bin, while the interval range distribution and the model of the MPS range do not affect the estimation accuracy significantly. Moreover, it is found that for hardware implementation, using three bits for the fractional part of the estimated bit length per bin in the rate estimation table is enough to obtain reasonable accuracy of rate estimation.